Sex-specific hypothalamic neural projection activity drives caregiving in mice - Ilaria Carta; Tushar Arora; Stefano Lutzu; Giovanni Podda; Gaspar Nicolay Vera Ortega; Stephanie Rudolph; Anita E. Autry (Nature Communications)
Abstract Infant care is critical for survival and healthy development. In laboratory mice, unmated males and females display infant-directed behavior ranging from neglect and aggression to alloparental care. Previous research suggests that excitatory neurons in the perifornical area of the hypothalamus (PeFA) mediate pup-directed aggression. Because medial preoptic area galanin-expressing (MPOAGal) neurons are indispensable for caregiving, we hypothesized that inhibitory MPOAGal projections to PeFA prevent pup-directed aggression. We found that MPOAGal→PeFA projection activity increased during pup approach in both sexes, and alloparental females showed increased projection activity during pup grooming compared to males. Anatomical differences did not explain this disparity in activity between sexes. Optogenetic inhibition of MPOAGal→PeFA projections reduced pup grooming in alloparental females but did not affect male caregiving, while projection stimulation reduced infant-directed aggression in males. Altogether, we show that this projection holds greater significance for female caregiving due to its heightened activity during natural behavior toward pups.